Descriptions of new and rare crabs associated with coral rubble and sponges from Kanyakumari, southeastern Arabian Sea, southern India (Decapoda: Brachyura: Epialtidae and Pilumnidae) - Ng, Peter K. L.; Prema, Mani; Ravichandran, Samuthirapandian (Zootaxa, 2024)
Three new brachyuran crab species are described from coral rubble and sponges collected in the southern Indian state of Tamil Nadu. The epialtid, Acanthophrys keeae n. sp., was obtained from coral rubble and is the first species from the genus reported from the Indian Ocean. It is most similar to A. costatus Griffin & Tranter 1986, from eastern Australia, but can be distinguished by the proportionately longer postorbital spine, more strongly granulated gastric region, relatively less inflated and narrower branchial region, sinuous outer margin of the basal antennal article which has the median part concave, almost smooth merus of the cheliped, more elongate male anterior thoracic sternum, more triangular male pleon, and the distal two-thirds of the male first gonopod being almost straight. The pilumnid, Latopilumnus ajmali n. sp., was found in the sponge, Callyspongia (Cladochalina) diffusa (Ridley, 1884), and is characterised by its carapace and pereiopods being covered by a relatively dense coat of short setae with only scattered simple long setae, and the dorsal carapace surface being almost smooth with the regions poorly demarcated. Vellumnus intonsus n. sp. (Pilumnidae) was present in coral rubble, is morphologically most similar to V. penicillatus (Gordon, 1930) (Hong Kong) and V. pygmaeus Takeda, 1977 (Japan) but can be separated by the lateral lobule of the front being separated from the frontal lobes by a deep cleft, the more prominently convex supraorbital margin, triangular external orbital tooth, presence of larger granules on the cheliped carpus and chela, and the distal part of the male first gonopod is proportionately stouter and distinctly hooked.